2010
DOI: 10.4141/cjps10059
|View full text |Cite
|
Sign up to set email alerts
|

Performance of tropical early-maturing maize cultivars in multiple stress environments

Abstract: tropical early-maturing maize cultivars in multiple stress environments. Can. J. Plant Sci. 90: 831Á852. Maize (Zea mays L.) production in west Africa (WA) is constrained by drought, Striga hermonthica infestation and low soil nitrogen (N). Maize varieties resistant to Striga, drought, and low N are ideal for WA, but genotype )environment interaction on these traits are usually significant due to differential responses of cultivars to growing conditions. Three studies were conducted from 2007 to 2009 at five l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
31
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 23 publications
7
31
1
Order By: Relevance
“…To our knowledge, the only available studies employing such methodology are those conducted by Cirilo et al (2009);Badu-Apraku et al (2010) and Badu-Apraku et al (2011), in which genotypes with potentially aggregator alleles favorable for the efficient use of nitrogen were identified.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the only available studies employing such methodology are those conducted by Cirilo et al (2009);Badu-Apraku et al (2010) and Badu-Apraku et al (2011), in which genotypes with potentially aggregator alleles favorable for the efficient use of nitrogen were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Improvement for drought tolerance has most often resulted in specific adaptation and improved performance under low-N conditions, indicating that tolerance to either stress involves common adaptive mechanism (Bänziger et al, 1999;Badu-Apraku et al, 2011, 2015a. It is therefore becoming increasingly important to adopt a holistic approach to identify genotypes with tolerance to a range of stresses expected in the target environment in WCA instead of compartmentalizing different stresses (Badu-Apraku et al, 2010). During the past decade, the International Institute of Tropical Agriculture Maize Improvement Program (IITA-MIP) has therefore paid increasing attention and devoted scarce resources to develop new products endowed with high yield potential and stability across a broad range of moisture availability and growing conditions.…”
mentioning
confidence: 99%
“…It complements the results of the ANOVA in that, after the ANOVA had shown significant mean squares for GEI, GGE biplot graphically analyzes the nature of the interactions. The investigation into GEI becomes more interesting with the introduction of the concept of crossover interaction and GGE biplot has increasingly been used in GEI data analysis in agriculture (Yan et al 2000;Crossa et al 2002;Badu-Apraku et al 2010). For this type of analysis, Gauch (1992) reported that GGE biplot is superior to other multivariate statistical tools especially the Additive Main Effect and Multiplicative Interaction (AMMI) in that GGE biplot has many visual interpretations and it particularly allows visualization of crossover GEI.…”
Section: Multi-environment Analysismentioning
confidence: 99%